Interações medicamentosas relacionadas a associações de antimicrobianos em um hospital de média complexidade - Gaspar, Felipe Andrade (Brasil, 2021)
Objective:This study sought to identify potential drug interactions caused by the concomitant use of more than one antimicrobial that could compromise the safety of patients admitted to a medium-complexity hospital. Methods:This was a cross-sectional, retrospective study, carried out by analyzing the prescriptions of antimicrobials dispensed to patients hospitalized in a hospital, whose collected data were analyzed and interpreted using descriptive statistics and chi-square test, after approval by the CEP-UFAM (CAAE 01581318.2.0000.5020). Results:The variables showed a prevalence of hospitalizations in the medical clinic, female patients, beta-lactam prescriptions and drug interactions associated with the combined prescription of antimicrobials. It was also identified that drug interactions occurred mainly due to prescription errors and non-adherence to institutional clinical protocols. Conclusion:Therefore, it is necessary to consolidate the actions of the Hospital Infection Control Commission (CCIH), seeking to reduce the irrational use of antimicrobials, and consequently, to expand the safety standards for patients